Analysis of the Drivers of the Need for a Digital Wallet Post-Covid in Labuhanbatu Regency - Muhammad Dzaki Abdillah; P. Pristiyono; Abd. Halim (PT Mattawang Mediatama Solution, 2022)
The biggest hope of this research is to empirically review about new habits or habits related to the level of convenience of consumers in transacting using digital wallets. The population is people who are spread out in South Labuhanbatu Regency totaling 314,094 people, in determining the sample the author uses the Slovin formula approach so that a minimum sample size of 100 people will be tested for validity and reliability test data quality and data analysis using a path analysis approach with the IBM AMOS 22 application. All hypotheses proposed and the comparison results show that all hypotheses are accepted, so that the research has an accurate analysis of the proposed hypotheses, even the biggest influence in this study occurs between the convenience of online services and E-WoM.